TAFSIR MAQÂȘIDI AND THE EDUCATION EPISTEMOLOGY IN Q.S. AL-‘ALAQ: A Quranic Vision for Learning - Hasyim, Muhammad; Nashrullah, Nashrullah (Ulul Albab: Jurnal Studi Islam, 2025)
Q.S. al-Alaq [96]:1-5, widely regarded as the Quran’s first revelation, presents a foundational epistemological vision that emphasizes literacy, divine-human connection, and the pursuit of knowledge. More than a simple command to “read,” the passage constitutes an ethical and spiritual framework that remains deeply relevant in modern educational context, particularly amid the challenges posed by digital fragmentation, superficial information consumption, and declining spiritual orientation. This study critically examines the epistemology of Islamic education embedded in Q.S. Q.S. al-Alaq [96]:1-5 through the lens of Tafsîr Maqâidî, a purposive interpretive approach seeking to uncover the higher objectives (maqâșidî) of the text. Utilizing library research and comparative textual analysis, it engages classical and contemporary exegeses, including Tafsîr al-Țabarî, Tafsîr al-Qurțubî, Tafsîr al-Misbah, and the works of Ibn Âshûr and Jasser Auda. Three core contributions emerge. First, the study proposes a tawhîd-centered literacy paradigm that aligns reading with spiritual awareness. Second, it constructs an integrative epistemological model wherein revelation and reason (‘aql) are coequal sources of knowledge. Third, it frames moral responsibility and lifelong learning as essential components of Islamic educational philosophy. By articulating a spiritually grounded, purpose-driven vision of education, this study offers a timely and transformative response to the epistemic crises of the digital age. It contributes to contemporary Islamic educational discourse by reasserting the Quranic foundation for ethical, holistic, and forward-looking learning frameworks.